Physicochemical Characteristics and Microbial Communities in Gochujang, a Traditional Korean Fermented Hot Pepper Paste - Ryu, Jung-A; Kim, Eiseul; Kim, Mi-Ju; Lee, Shinyoung; Yoon, Sung-Ran; Ryu, Jung-gi; Kim, Hae-Yeong (Frontiers in Microbiology, 2021)
.Gochujang is a Korean fermented hot pepper paste beneficial to human health by providing various nutrients. In this study, its physicochemical characteristics were identified, and its microbial communities were analyzed by high-throughput sequencing. The interrelationship between physicochemical characteristics and microbial composition was investigated to reveal the properties of gochujang before and after fermentation. After fermentation, all samples showed decreased salt concentration, pH, and reducing sugar content, while the acidity and amino-type nitrogen increased. The water content, salt concentration, amino-type nitrogen, and reducing sugar differed according to the batches of samples. Bacillus, Aerosakkonema, and Enterococcus were identified as the predominant bacterial genera. Furthermore, Aerosakkonema was the most abundant genus before fermentation; however, it was replaced by Bacillus as it decreased after fermentation. For the fungi, Aspergillus dominated before fermentation, whereas Zygosaccharomyces and Millerozyma dominated after fermentation. The high level of amino-type nitrogen in gochujang was related to the relative abundance of B. haynesii/B. licheniformis before fermentation. Additionally, the high abundance of Z. rouxii after fermentation was related to the flavor of gochujang. This comprehensive analysis of the microbial community associated with the physicochemical properties of gochujang could help in understanding the factors affecting the quality of the product.